Determination of Flavanones in Orange Juices Obtained from Different Sources by HPLC/DAD - Lidércia C. R. Cerqueira e Silva; Jorge M. David; Rafael dos S. Q. Borges; Sérgio L. C. Ferreira; Juceni P. David; Pedro S. dos Reis; Roy E. Bruns (Journal of Analytical Methods in Chemistry)
Flavanones (hesperidin, naringenin, naringin, and poncirin) in industrial, hand-squeezed orange juices and from fresh-in-squeeze machines orange juices were determined by HPLC/DAD analysis using a previously described liquid-liquid extraction method. Method validation including the accuracy was performed by using recovery tests. Samples (36) collected from different Brazilian locations and brands were analyzed. Concentrations were determined using an external standard curve. The limits of detection (LOD) and the limits of quantification (LOQ) calculated were 0.0037, 1.87, 0.0147, and 0.0066 mg 100 g−1 and 0.0089, 7.84, 0.0302, and 0.0200 mg 100 g−1 for naringin, hesperidin, poncirin, and naringenin, respectively. The results demonstrated that hesperidin was present at the highest concentration levels, especially in the industrial orange juices. Its average content and concentration range were 69.85 and 18.80–139.00 mg 100 g−1. The other flavanones showed the lowest concentration levels. The average contents and concentration ranges found were 0.019, 0.01–0.30, and 0.12 and 0.1–0.17, 0.13, and 0.01–0.36 mg 100 g−1, respectively. The results were also evaluated using the principal component analysis (PCA) multivariate analysis technique which showed that poncirin, naringenin, and naringin were the principal elements that contributed to the variability in the sample concentrations.